2005
DOI: 10.1152/ajpgi.00091.2005
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of histone acetyltransferase (HAT) in ethanol-induced acetylation of histone H3 in hepatocytes: potential mechanism for gene expression

Abstract: Ethanol treatment increases gene expression in the liver through mechanisms that are not clearly understood. Histone acetylation has been shown to induce transcriptional activation. We have investigated the characteristics and mechanisms of ethanol-induced histone H3 acetylation in rat hepatocytes. Immunocytochemical and immunoblot analysis revealed that ethanol treatment significantly increased H3 acetylation at Lys9 with negligible effects at Lys14, -18, and -23. Acute in vivo administration of alcohol in ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
117
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(123 citation statements)
references
References 59 publications
3
117
0
Order By: Relevance
“…Park et al (2005) found that both MEK and JNK pathways' inhibitors, but not p38, prevented the ethanol-induced increase in histone 3 lysine 9 acetylation. We therefore measured the levels of NFκB p65, p38, pJNK, p-AKT, and pErk1/pErk2 in the nuclear extracts from livers at the peaks and troughs of the UAL cycle.…”
Section: Resultsmentioning
confidence: 90%
See 3 more Smart Citations
“…Park et al (2005) found that both MEK and JNK pathways' inhibitors, but not p38, prevented the ethanol-induced increase in histone 3 lysine 9 acetylation. We therefore measured the levels of NFκB p65, p38, pJNK, p-AKT, and pErk1/pErk2 in the nuclear extracts from livers at the peaks and troughs of the UAL cycle.…”
Section: Resultsmentioning
confidence: 90%
“…Figure 3 shows that there was an increase in histone 3 lysine 9 acetylation at the peaks of the UAL cycle after chronic ethanol feeding. It was previously reported that there was an increase in histone 3 lysine 9 acetylation in acute ethanol exposure experiments (Park et al 2003(Park et al , 2005. This indicates that histone acetyltransferase (HAT) activity is increased, and that the histone acetyltransferase p300 may be responsible for this increased activity.…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…This effect has been observed in isolated hepatocytes and in rat liver after both acute and chronic ethanol exposure [8,[17][18][19][20][21] . Although histone H3 encodes at least four acetylated lysines (lys 9, 14, 18 and 23), acetylation of lysine 9 is selectively increased after exposure to physiological ethanol concentrations [8] .…”
Section: Histone H3mentioning
confidence: 99%